Altitude-specific differences in tree-ring δ2H records of wood lignin methoxy in the Qinling mountains, central China. (15th January 2023) - Lu, Qiangqiang; Liu, Xiaohong; Treydte, Kerstin; Greule, Markus; Wieland, Anna; Liu, Jinzhao; Zhao, Liangju; Zhang, Yu; Kang, Huhu; Zhang, Lingnan; Zeng, Xiaomin; Keppler, Frank; et al.
Abstract: The Qinling Mountains (Qinling Mts.) are characterized as a distinct transition of bioclimatic zones along the north-south geographic boundary in China. Although ongoing global warming may affect the growth of most tree species across elevation gradients, the effect of modern warming on the stable hydrogen isotopes of tree-ring wood is still unknown. In this study, we developed early- and late-wood δ 2 H chronologies from 1900 to 2018 CE of lignin methoxy groups ( δ 2 HLM ) at 700-m intervals from 1700 to 3100 m a.s.l. along the elevation gradient in Mount Taibai (Mt. Taibai), the peak of the Qinling Mts. The δ 2 HLM values of the earlywood were relatively enriched in 2 H compared to the latewood, and an elevation-dependent depleting trend along the altitudinal gradient was observed. Comparing the δ 2 HLM values with modelled δ 2 H values of precipitation ( δ 2 HPre ) of the sample sites, similar isotopic patterns can be obtained. The reconstructions of δ 2 HPre values confirm the strong coherence between the isotopic composition of the source water and the methoxy groups in the growing season. The consistency of δ 2 HLM chronologies between the early- and late-wood at the higher sites was stronger than that at the lower sites. The additional lagged effect and climate response revealed significant seasonal and altitudinal differences. At the timberline site, δ 2 HLM values of earlywood were mainly related to the January and February temperatures, whereas δ 2 HLM values of latewood correlated most strongly with temperature from July to September, and both values were controlled by the amount of total precipitation. In addition, the combined new δ 2 HLM chronologies, based on the lag-1 autocorrelation and the weighted average of the current year earlywood and previous latewood, could be used to merge the corresponding temperature signals from the middle- and low-elevation sites. Altitudinal correlations of elevation offset between the annual δ 2 HLM chronologies and interpolations of precipitation and temperature suggested that the δ 2 HLM values at higher elevations better represent regional climatic changes. Therefore, topographic effects such as elevation differences should be considered in large-scale applications of δ 2 HLM values in future studies. Highlights: Altitude- and seasonal-differences in δ 2 H values of both tree-ring wood and precipitation were revealed in Qinling Mountains, China. Elevational effects of temperature and precipitation resulted in the variations of δ 2 HLM of lignin methoxy. Timberline δ 2 HLM recorded the significantly lagged effects and strong hydroclimatic signals. Altitude specificity of δ 2 HLM should be considered in the large-scale investigations.